2017
DOI: 10.1155/2017/5279065
|View full text |Cite
|
Sign up to set email alerts
|

Ribonuclease fromBacillusActs as an Antiviral Agent against Negative- and Positive-Sense Single Stranded Human Respiratory RNA Viruses

Abstract: Bacillus pumilus ribonuclease (binase) was shown to be a promising antiviral agent in animal models and cell cultures. However, the mode of its antiviral action remains unknown. To assess the binase effect on intracellular viral RNA we have selected single stranded negative- and positive-sense RNA viruses, influenza virus, and rhinovirus, respectively, which annually cause respiratory illnesses and are characterized by high contagious nature, mutation rate, and antigen variability. We have shown that binase ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Nevertheless, mechanisms underlying the anti-viral effects of binase remain unclear. We had previously shown that pre-treatment of IAV with binase before infection of A549 and MDCK-II cells resulted in an anti-viral effect that was dependent on the amount of binase [ 13 , 21 , 22 ]. Furthermore, we reported that binase degrades vRNA, which is not protected by the virion/RNP complex and that binase added to cells (HEK293, A549) reduces of a GFP reporter gene expression by a transient IAV mini-genome system [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, mechanisms underlying the anti-viral effects of binase remain unclear. We had previously shown that pre-treatment of IAV with binase before infection of A549 and MDCK-II cells resulted in an anti-viral effect that was dependent on the amount of binase [ 13 , 21 , 22 ]. Furthermore, we reported that binase degrades vRNA, which is not protected by the virion/RNP complex and that binase added to cells (HEK293, A549) reduces of a GFP reporter gene expression by a transient IAV mini-genome system [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…We had previously shown that pre-treatment of IAV with binase before infection of A549 and MDCK-II cells resulted in an anti-viral effect that was dependent on the amount of binase [ 13 , 21 , 22 ]. Furthermore, we reported that binase degrades vRNA, which is not protected by the virion/RNP complex and that binase added to cells (HEK293, A549) reduces of a GFP reporter gene expression by a transient IAV mini-genome system [ 21 , 22 ]. Moreover, we showed that binase is able to penetrate into A549 cells [ 23 ] and that treatment of IAV-infected A549 cells led to titer reduction and reduced the viral NP mRNA amount 12 h post-infection (h p.i.)…”
Section: Introductionmentioning
confidence: 99%
“…Secretion of low-molecular-weight guanyl-preferring ribonucleases (RNases) is a distinct feature of some Bacillus species ( Ulyanova et al, 2016 ). A well-studied representative of these RNases, binase from B. pumilus , has manifested antitumor ( Ulyanova et al, 2011 ; Cabrera-Fuentes et al, 2013 ; Mitkevich et al, 2013 ) and antiviral activities ( Shah Mahmud and Ilinskaya, 2013 ; Ilinskaya and Shah Mahmud, 2014 ; Shah Mahmud et al, 2016 , 2017 ; Müller et al, 2017 ). KRAS which has mutations in about 40% of patients with colorectal cancer ( Prior et al, 2012 ) was shown to be a direct target for antitumor binase ( Ilinskaya et al, 2016 ).…”
Section: Under-appreciated Components Of Bacilli Smentioning
confidence: 99%
“…Low concentrations of RNases stimulate plant growth and resistance to a broad spectrum of stress factors, high levels of them show antiviral properties by destroying viral RNA. Microbial RNases are potential therapeutic agents which are suggested for the treatment of human viral diseases (Mahmud et al, 2017). In this regard, the identification of the biological properties of endophytic Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%